LEGAL PROTECTION FOR ONLINE ARISAN ADMINS INVOLVING MINORS FROM A CIVIL LAW PERSPECTIVE - Ruchbana, Kissy (Inspiring Law Journal, 2025)
Online arisan agreements made by incompetent people can be canceled based on the will of the other party who feels aggrieved. The regulation of online arisan agreements in Indonesia is not specifically regulated by certain laws but is based on several provisions, namely the Civil Code, namely in Article 1320 of the Civil Code concerning the valid conditions of the agreement, Article 1338 of the Civil Code concerning the principle of freedom of contract, Article 1354 concerning borrowing and lending. Law Number 1 of 2024 concerning amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions. The legal consequences of default on online arisan agreements made by minors are based on Article 1367 of the Civil Code which states that parents are responsible for committing defaults in online arisan involving minors to pay compensation and this is in accordance with the provisions of Article 1243 of the Civil Code regulating compensation for costs, losses, and interest due to default. Legal protection for the admin managing the arisan against arisan default by minors is to have the right to receive compensation for failure to fulfill the performance based on Article 1243 of the Civil Code which regulates the replacement of costs, losses, and interest due to default.